Diabetes mellitus and cardiovascular mortality across the spectrum of aortic stenosis. Issue 22 (13th June 2022) - Coisne, Augustin; Montaigne, David; Ninni, Sandro; Lamblin, Nicolas; Lemesle, Gilles; Delsart, Pascal; Filiot, Alexandre; Andrey, Paul; Balaye, Pierre; Butruille, Laura; Decoin, Raphael; Woitrain, Eloise; et al.
Abstract : Objective: Current data regarding the impact of diabetes mellitus (DM) on cardiovascular mortality in patients with aortic stenosis (AS) are restricted to severe AS or aortic valve replacement (AVR) trials. We aimed to investigate cardiovascular mortality according to DM across the entire spectrum of outpatients with AS. Methods: Between May 2016 and December 2017, patients with mild (peak aortic velocity=2.5–2.9 m/s), moderate (3–3.9 m/s) and severe (≥4 m/s) AS graded by echocardiography were included during outpatient cardiology visits in the Nord-Pas-de-Calais region in France and followed-up for modes of death between May 2018 and August 2020. Results: Among 2703 patients, 820 (30.3%) had DM, mean age was 76±10.8 years with 46.6% of women and a relatively high prevalence of underlying cardiovascular diseases. There were 200 cardiovascular deaths prior to AVR during the 2.1 years (IQR 1.4–2.7) follow-up period. In adjusted analyses, DM was significantly associated with cardiovascular mortality (HR=1.40, 95% CI 1.04 to 1.89; p=0.029). In mild or moderate AS, the cardiovascular mortality of patients with diabetes was similar to that of patients without diabetes. In severe AS, DM was associated with higher cardiovascular mortality (HR=2.65, 95% CI 1.50 to 4.68; p=0.001). This was almost exclusively related to a higher risk of death from heart failure (HR=2.61, 95% CI 1.15 to 5.92; p=0.022) and sudden death (HR=3.33, 95% CI 1.28 to 8.67; p=0.014). Conclusion: The effect of DM on cardiovascular mortality varied across AS severity. Despite no association between DM and outcomes in patients with mild/moderate AS, DM was strongly associated with death from heart failure and sudden death in patients with severe AS.